Detection of a new X-ray outburst from the SMC Be/X-ray binary Swift J010745.0-722740, confirming the 1180 d orbital period - Vasilopoulos, G.; Haberl, F.; Maggi, P. (2017)
Swift_J010745.0-722740 is a BeXRB candidate located in the SMC (ATel #5778) with no X-ray pulsations detected so far. Its companion exhibits strong (0.3-0.4 mag) outbursts, with a recurring time of 1180 d (ATel #5781, #5778).
Keywords: Binary; Neutron Star; Pulsar; Transient